Comparative effects of methanol and oil extracts of Ocimum gratissimum on testicular morphology and epididymal sperm reserve of adult male albino rats (Wistar strain). (2019) - Joseph, Ikokide Emmanuel; Jaja, Ishmael Festus; Boyi, Adamu Hamman; Olugbenga, Oyeyemi Mathew
Graphical abstract: Highlights: Ocimum gratissimum (OG) did not affect the sperm liveability and concentration of wister rat. Ocimum gratissimum had no significant difference in the body weight, epididymal weight, left and right testes weight compared with the control group. Mean testosterone level did not differ in all group treated with OG. No overt pathological lesions were apparent in the seminiferous epithelia or the interstitial spaces of the testes. Abstract: Fertility control with medicinal plants has been reported in the ancient and modern medical literature. In this research, the effects of methanol and oil extracts of Ocimum gratissimum (OG) on testicular morphology and epididymal sperm reserve were investigated in adult male Wistar rats. Fifty-five rats divided into 5 groups A-E of 11 rats each was used for this study. Methanol and oil extracts of Ocimum gratissimum were administered at two doses 250 and 500 mg/kg for 28 days. Animals in control group A received distilled water for the same duration. At day 14 and 28 of the study, five animals were sacrificed from each group, and their blood and testes samples were collected for the analysis. Spermiogram, testicular biometry, serum testosterone assay, and testicular morphology were assessed from harvested testes. The results revealed that there was no significant difference (p > 0.05) in serum testosterone level. There was also no significant difference (p > 0.05) in sperm volume, livability and abnormalities but there was significant differences (p < 0.05) in the sperm motility and concentration. Testicular biometry and testicular morphology between control and treated groups did not reveal any significant differences (p > 0.05). The study showed that methanol and oil extracts of Ocimum gratissimum (OG) did not have any inhibitory effect on the reproductive function and fertility of adult male albino rats. Further works should be carried out on isolated active fractions of this plant on male fertility.